"Both sides told," or, Southern California as it is ... - Vail, Mary C. (Pasadena, Calif., West coast pub. co., 1888)
Mary C. Vail was a resident of Southern California. "Both sides told" (1888) is a pamphlet written by Vail to provide an accurate but cautionary description of Southern California as an antidote to the unrealistic claims that had accompanied the region's real estate boom and bust of the 1880s. She warns of the sandstorms and dust in an area where drinking water must usually be piped in many miles and many crops will demand irrigation. Admitting that her home region is not a paradise, she points out that its climate remains healthful and that opportunities remain for those willing to work.
Also available in digital form on the Library of Congress Web site.
Keywords: California, Southern -- Description and travel; Women -- California; Urbanization -- California; Real estate development -- California; Agriculture -- California; Business -- California